PRAKTIKALITAS LKPD BERBASIS PBL BERDIFERNSIASI PADA MATERI VEKTOR - Fatma Wati; Sefna Rismen; Mulia Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the practicality of differentiated PBL-based Student Worksheets (LKPD) on vector material. This study is expected to help students learn independently and improve problem-solving skills. This research is a development research (R&D) using ADDIE, which consists of five stages: analysis, design, development, implementation and evaluation. The subjects of this study were students of moving class XI SMAN 1 Salimpaung in the 2025/2026 academic year. The instruments used in this study were questionnaires and learning outcome tests. The practicality score for this development research from the results of students was 91.7%, while from the results of educators it reached 97.2% which is categorized as very practical.